Konflik Sosial dalam Novel Segala Yang Diisap Langit Karya Pinto Anugrah - Oktaviolanda; Nurizzati Nurizzati (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
This study aims to classify: (1) the forms of social conflict in Pinto Anugrah's novel Everything is Smoked by the Sky, (2) the causes of social conflict in Pinto Anugrah's novel Everything is Smoked by the Sky, (3) the impact of social conflict in the novel Everything The Sky Suckes by Pinto Anugrah. The object of this research is the novel Everything Sucked by the Sky by Pinto Anugrah which will be published in 2021. This research uses a descriptive method. In collecting the data used in this study in the form of words, phrases, clauses and sentences that show the forms, causes, and impacts of social conflict in Pinto Anugrah's novel 'Everything That Is Smoked by the Sky'. The research instrument was the author himself using the help of another instrument in the form of a recording sheet. The data collection techniques used were reading and understanding the novel, conducting literature studies, determining the main character, and searching for and recording data related to the research problems contained in the novel. Data validation technique is using triangulation technique. The data analysis technique used is identifying and classifying data. Then interpret the data, and conclude the data analysis. The results of the study state (1) the forms of social conflict in Pinto Anugrah's novel Everything is Smoked by the Sky are personal conflicts, group conflicts, and conflicts within society. (2) the causes of social conflict in Pinto Anugrah's novel Everything is Sucked by the Sky are caused by differences between individuals or individuals, differences in social class, as well as differences in interests, and social change. (3) the impact of social conflict in Pinto Anugrah's novel 'Everything That Is Smoked by the Sky' includes the destruction of group unity, personality changes, and the destruction of social values and norms.